Managing patients who are immunocompromised during the COVID-19 pandemic. Issue 12 (December 2022) - Pullen, Richard L.
Abstract: The COVID-19 pandemic has caused distinct challenges for immunocompromised populations, including disease and social management. This article presents strategies to prevent infection and promote quality of life in patients who are immunocompromised. Abstract : The COVID-19 pandemic has caused distinct challenges for immunocompromised populations, including disease and social management. This article presents strategies to prevent infection and promote quality of life in patients who are immunocompromised.